Too much, too little, or too volatile? International capital flows to developing countries in the 1990s - Peter Nunnenkamp (Kiel Institute of World Economics (IfW), 2001)
Developing countries are constrained in financing current account deficits as real capital mobility is still far from perfect. At the same time, capital flows to these countries proved to be extremely volatile. The paper argues that the long-term problem of "too little" should not be confused with the short-term problem of "too volatile". The former is related to sovereign risk, which may be difficult to overcome. The latter could be kept within limits by financial restructuring towards relatively stable types of capital flows.
Keywords: F21; F32; G15; 330; developing countries; debt; equity investment; sovereign risk; volatility; international capital markets; Internationale Kapitalmobilität; Kapitalimport; Auslandsverschuldung; Volatilität; Direktinvestition; Länderrisiko; Entwicklungsländer